"But the science we do here matters": Youth‐authored cases of consequential learning. Issue 5 (3rd July 2017) - Birmingham, Daniel; Calabrese Barton, Angela; McDaniel, Autumn; Jones, Jalah; Turner, Camryn; Rogers, Angel
Abstract: In this paper, we use the concept of consequential learning to frame our exploration of what makes learning and doing science matter for youth from nondominant communities, as well as the barriers these youth must confront in working toward consequential ends. Data are derived from multimodal cases authored by four females from nondominant communities that present an account of "science that matters" from their work during their middle school years. We argue that consequential learning in science for these girls involves engaging science with a commitment to their community . This form of engagement required the girls to develop bridging practices that allowed them to transform existing relationships among science and community for themselves and others despite normative barriers experienced in science. Our study expands upon current understandings of consequential learning through highlighting the vital role of sociohistorically constructed understandings of community in determining when, how, and why science learning and doing matters for youth. This view opens up new ways to understand how youth can and do contribute to the changing contexts in which science takes place, and toward the ways in which youth contributions alter what gets counted as learning, as being expert, and as meaningful participation.